Research of Fatigue Life of Spinning Pulley Under Different Cycle Characteristics - Weng Jiancheng (Jixie chuandong)
Taking spinning pulley with a slit in the automobile booster pump as study object,the stress limit diagram with different cycle characteristics are discussed. The fatigue life of spinning pulley under the complexity of the stress are assessed by using the stress limit diagrams and safety factor method by ANSYS. The results show that,the spinning pulley with a slit in the automobile booster pump are in different cycle characteristics and complex state of alternating stress,but it works safely. The reliable basis is provided for designing fatigue life of the actual spinning pulley without S-N data.